Beberapa sifat, asal usul dan kepengarangan peribahasa Melayu - Ding, Choo Ming (Universiti Kebangsaan Malaysia, 2009)
Characterized by beautiful rhymes and reflecting the profound thought and imagination of the Malay people from time immemorial, Malay proverbs, used in this study as a generic term to include peribahasa, simpulan bahasa, bidalan, petitih and perbilangan, are yet another genre of Malay literature of unique creation. The bulk of the research is on the principles and methods of their authorship, which is defined as how the various Malay proverbs were created, recreated and circulated through space and time. By learning the rules, they were familiar with the style, structure, rhythm, content and language norms of Malay proverbs. The interesting point is these rules gave them space for their creativity. Subsequently, they have shown their individual creativity in the variety of the proverbs. In the process, they made use of the various mnemonic devices, useful in folklore literature